F2MoC: A Preliminary Product Line DSL for Mobile Robots - Durelli, Rafael S.; Durelli, Vinicius H. S. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
SPL and MDD have been drawing increased attention from the software community. In the literature it is possible to find a set of articles that apply MDD techniques to assist the development of a SPL. Objectives: To show how to create a DSL based on a feature model. Methods: A SPL and MDD techniques were used to create a DSL. Results: A DSL was developed in order to assist the development of the mobile robots. Conclusions: Advantages can be gained from using the DSL: (i) an easier instantiation of SPL members; (ii) it is possible for the engineers to focus on an high level model (i.e., features model), obviating the need of dealing with platform-specific issues; (iii) source code is generated automatically from this high level model.